Pembelajaran Pendidikan Agama Islam Berbasis Pengembangan Bahan Ajar Mind Mapping dalam Meningkatkan Motivasi Belajar Siswa di SMK Haqqul Yaqin Sampang - Rahmawati, Rahmawati; Jihad, Moh. Iqbal Fachrullah Abul; Zainab, Nurul (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
Mind mapping-based teaching materials are a development of the PAI learning process as a teaching material product aimed at assisting students with efforts to motivate and make it easier for students to know and understand PAI subject matter. Researchers use development research or Research and Development (R&D). The research design uses the ADDIE instructional model as a teaching process including several stages of analysis, design, development, implementation, and evaluation. The results of the research on the feasibility of teaching materials based on material experts, have been categorized as feasible from the assessment of material experts obtained 90% classified as very valid, which can be used as teaching materials. Meanwhile, the feasibility of teaching materials based on teaching material experts obtained 75% is quite valid, which can be used as teaching material during the teaching and learning process. Then, supported by the feasibility of teaching materials based on student assessment, it is classified as adequate or feasible to use, it can be seen based on the percentage obtained by the answer "yes" 90%. Furthermore, mind mapping-based PAI teaching materials are uploaded via the YouTube platform so that students can access them without being limited by time and place. Thus, it can facilitate students in learning PAI material to perfect religion through Hajj and Umrah and can increase student learning motivation. It can be seen from the questionnaire percentage number is 90%, classified based on the level of practicality is very practical.